129 HYPERCALCEMIA IN END-STAGE RENAL DISEASE: JANUS'S WISDOM INVOKED!. (1st January 2006) - Sequeira, A.; Patel, P.; Laborde, J.; Leblanc, B.; Carter, M.; Alexander, N.; Blondin, J.
Abstract : Introduction: End-stage renal disease (ESRD) patients have hyperplastic hyperparathyroid glands. We present a case where administration of calcimimetics unmasked underlying autonomous parathyroids. Case: A 43 yo male with ESRD on hemodialysis for 15 years, s/p transplant, was admitted for evaluation of symptomatic hypercalcemia. Over the last 10 months, his biointact parathyroid hormone levels (biPTH) ranged between 500 and 600 (80-160 pg/mL). Five months prior to admission, he had been started on cinacalcet and paricalcitol. Since then, his calcium and phosphorus ranged between 9.9 and 11.9 and 5.3 and 7.7 mg/dL, respectively, with elevated biPTH. Labs on admission (post hemodialysis) were Ca 14.8 mg/dL, phos 5.8 mg/dL, alk phos 96 U/L, and albumin 3.1 mg/dL. With a possibility of drug-induced hypercalcemia the above-mentioned medications and calcium acetate were stopped. Other data obtained were intact PTH 451 (iPTH 8-74 pg/mL), PTHrP < 2.5 (< 1.4 pmol/L), 1, 25 vit D 84.6 (15.9-55.6 pg/mL), 25 vit D 7 (8.9-4.7 ng/mL), a normal serum immunoelectrophoresis, and a negative PPD. A chest CT and abdominal ultrasound were unremarkable. A bone scan revealed increased uptake in the skull. He was started on parenteral calcitonin and dialyzed regularly over the next several days. However, his calcium remained between 14 and16 mg/dL. His 1, 25 vit D level dropped to < 5. At parathyroidectomy, a 600 mg right lower lobe adenoma was removed. The remaining parathyroid glands appeared normal. The iPTH failed to normalize. A sestamibi scan revealed the presence of an accessory gland along the left sternocleidomastoid. A 1.58 g adenoma was resected from within the muscle. His iPTH immediately decreased to 29 pg/mL. Discussion: Vitamin D analogues and cinacalcet have been approved for the management of hyperparathyroidism in ESRD. The persistence of an elevated PTH, in spite of calcimimetics, should raise suspicion of an autonomous change. A fifth parathyroid gland is present in 3-5% of the population. This should always be suspected when PTH fails to fall in spite of removal of an adenoma or in the presence of normal-sized glands.